RISK MANAGEMENT FOR INSTRUCTIONAL DESIGN ELEARNING IN HIGHER EDUCATION - Muhammad Rozahi Istambul; Ucu Nugraha (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The education process during the Covid-19 pandemic greatly affected learning patterns at various levels, especially universities. Various rules regarding face-to-face interaction in class are clearly not recommended to avoid the emergence of a new covid-19 cluster. This causes no other choice, except to take advantage of the online learning process. Various uses of technology and platforms can be selected according to the policies of each university. Risk management for the online learning process needs to be managed properly because the main thing that needs to be obtained from the implementation of an eLearning rule is that the achievement of the expected competency abilities for students. Risk management, in this case, is more focused on management efforts made related to instructional design in the learning process so that learning outcomes can be measured according to outcome-based education. The influence of instructional design that is designed will also affect the motivation and efforts of students in carrying out various activities. This research was conducted in 2 different types of subjects with the same students. The result will be obtained through several learning activities carried out every week and or learning achievement targets that are used as goals for students.